KEPUTUSAN KONSUMEN DALAM MEMBELI DAGING BROILER ERA PASCA PANDEMI COVID-19 DI KABUPATEN MALANG - Ariani Trisna Murti; Hidayati Karamina; Indryani Malo (BUANA SAINS, 2022)
This study aimed was to determine the factors that influence consumers in buying broiler meat partially and simultaneously at the Landungsari Market, Malang Regency. The independent variables studied were the price of broiler meat, chicken meat free-range price, the price of broiler eggs, promotion, service, and location. Dependent on the variable in this study is consumer purchasing decisions consisting of consumer satisfaction, consumer loyalty, and giving recommendations to others to come to buy broiler meat at the Landungsari Market. The data used in the research are primary data and secondary data. The data was obtained from the tabulation of raw data through a questionnaire of 100 respondents and analyzed using multiple linear regression analysis. The result shows that all factors in the research variables correlate with consumers buying broiler meat at the Landungsari Market. The most dominant variable is free-range chicken meat price has become a partial influence on consumer purchasing decisions in buying broiler meat at the Landungsari Market. Variable factors that influence simultaneously or together sequentially according to the percentage value are free-range chicken meat, the broiler meat price, service, egg price, location of purchase, and promotional factors. All variables give a positive contribution and influence together of 0.511 with a tolerance limit of 0.05%.